Optimalization of Revenue Forecasting in the Security of the Parliament - Sofya A. Rasyid; Marliyah Marliyah (Universitas Muhammadiyah Palu, 2020)
Currently, the government of the Parigi Moutong Regency has sought to facilitate access to community forest plants that are truly managed by the community rather than the financiers.